(3CSQGQ ePgdIs - (3aQjb JMQjQ hLhgs; (3hLhg ddEfJGL GdEYdGejs ((3GdQjGVs (3OGQ hLhg ddfTQ hGdJhRjYs, 2011)
(3GdMjGI edjFI HGdYLGFH (B.. (3hGdYGde ef MhdfG jYL HGdZQGFH(B.. (3hYfOeG JQOfG eYdheI Ch WQaI efgG, JfJGHfG eRjL ef eTGYQ GdPghd hGdOgTI hGdThb deYQaI GdeRjO hGdeRjO efgG (B.. (3gcPG gh GdEfSGf(B. (3GdCMOGK hGdCQbGe hGdEMUGAGJ hGdeQhjGJ hGdeYdheGJ hGdCSQGQ hGdMbGFb GdCcKQ OgTI hZQGHI, Yf GdWHjYI (B.. (3Yf GdEfSGf (B.. (3Yf GdMjhGf (B.. (3Yf cd eG jMjW HfG gh eG MGhdfG QUOg aj gPG GdcJGH(B. (3hHgPG GdEUOGQ (B: (3jSJWjY cd aQO aj GdCSQI Ohf GSJKfGA Cf jVja Edi ecJHJg eUOQG eejRG ef eUGOQ GdaGFOI hGdJSdjI aj bGdH ef GdeQM hGdWQGaIs
(3GdYGde ef MhdfGs
Keywords: (3GdeYGQa GdYGeIs